Pelatihan Mendesain Animasi 3D Kupu-Kupu Untuk Meningkatkan Daya Tarik Calon Mahasiswa Pada Prodi Teknologi Komputer - Ayuningsih, Ekatri; Ibrahim; Rahmah, Maulidya; Syah, Andry; Hafiz, Muharsyah Hafiz; Surbakti, Eka Wulandari; Hahum, Zubaidah (Jurnal Masyarakat Indonesia (Jumas), 2023)
Vocational high school students who have graduated from vocatonal hight school always have difficulty deciding between going straight to work or continuing their studies. Major selection is included in the educational process, which has the scope of determining future career success. The study program chosen must be in accordance with the interests and abilities possessed by students. This community service trains vocational or high school students to gain skills in designing a 3D butterfly animation. This community service aims to promote the Computer Technology Study Program to SMK or SMA students so that they are interested in registering at the Medan LP3I Polytechnic. The method used is the lecture and training method. The Powepoint 2019 application is used in the material, while the 3D Max Application is used to design butterfly animations